Strategi Integrasi Energi Terbarukan Berbasis Smart Grid untuk Mewujudkan Sistem Energi Listrik yang Berkelanjutan di Indonesia - Muhammad Dicky Saputra; Apipah Apipah; Muhammad Aldi Firdaus; Muhammad Rizki; Didik Aribowo (Prosiding Seminar Nasional Ilmu Pendidikan, 2025)
Indonesia has abundant renewable energy potential, but its utilization still faces various technical, economic, social, and policy barriers. This article examines renewable energy integration strategies through a smart grid approach as a systemic solution to build a reliable, efficient and sustainable electricity system. Using a literature review method, it highlights key challenges such as intermittency of energy sources, limited storage infrastructure, high initial investment costs, and regulatory and social resistance. The integration strategies discussed include the development of energy storage technologies, increased flexibility of the electricity system, optimization of plant planning and operations, energy policy reform, and investment in infrastructure and digitalization. The vital role of smart grids is made clear through case studies of implementations in remote areas that have successfully improved distribution efficiency and community participation. The results confirm that successful integration of renewable energy requires synergy between technology, policy, and active community involvement. In conclusion, smart grid is not just a technological infrastructure, but the foundation of transformation towards a national energy system that is low-emission, inclusive, and long-term resilient.